Kajian Tekno-Ekonomi Produksi Reaktor Pirolisis dalam Menghasilkan Bioarang dan Asap Cair - Kemas Ridhuan; Dwi Irawan; Yulita Zanaria (Universitas Muhammadiyah Metro, 2019)
The techno-economy of pyrolysis products is very important because it is related to the profit and loss of production business. On the other hand, this product is very potential and good prospect, due to it can generate energy from wasted and problematic environmental waste. In addition, the equipment is very simple and very easy to make, maintain and operate, it does not require a large cost or capital. The research objective is to determine the economic value and BEP (Break Even Point) of pyrolysis combustion in producing liquid smoke and bio charcoal with biomass raw materials. Figure the characteristics of liquid smoke and bio-charcoal obtained such as heat value, pH, acid, specific gravity, viscosity, and color. The method used is initiated by testing the pyrolysis reactor, at this stage bio-charcoal products and liquid smoke are obtained, influenced by such as pyrolysis temperature, processing time and equipment. Followed by making bio charcoal briquette, this stage is mashed charcoal, making dough or packing, drying, then printing briquettes. And finally the process of re-liquidation of liquid smoke, by means of redestilation or continued heating so that it will produce liquid smoke grade 3, grade 2, and grade 1. The results obtained are known to have an economic cost of Rp. 244.720.000, and for equipment depreciation costs Rp. 144.839.000. For the cost of production per year, that is Rp. 100.925.000 and for the variable cost per kg, which is Rp. 4.888/kg. The initial capital required is Rp. 129.839.000. For the production cost of Rp. 7.476/kg. For the total price of sales is Rp. 100.939.306 and for BEP (Rp) which is Rp. 100.939.306 and BEP (kg) which is Rp. 13.495/kg. Keywords: BEP, economy, pyrolysis, bio charcoal, liquid smoke.